Study on Solar PV Power Output during Grid Voltage Dip/Swell - Mohamad, Nurhusna Millah (2018)
This paper studies the solar photovoltaic power output during grid voltage dip/swell. The introduction of renewable energy source embedded in AC network system is inevitably subjected to power quality related problem such as voltage dip and voltage swell. It is very important to study on solar photovoltaic power output during grid voltage dip and swell because it will effect the quantum of power feed into the grid system. The objective of this study are to establish photovoltaic power output with constant grid voltage and to analyze photovoltaic power output during grid voltage dip and swell. This study will be carried out experimentally at lab under control constant irradiation. The voltage dip and swell simulator connected directly to grid power supply. Solar photovoltaic panel and inverter will be connected to the voltage dip and swell simulator. The voltage and current of the solar photovoltaic need to be measured at the voltage dip and swell simulator by using power quality analyzer. As the results, we can see the time taken of solar photovoltaic output power decreasing and increasing back that effect of grid voltage dip and swell.